The Web Application Survey Software for virtual landscape character survey tool - Abdullah, Alias; Hj. Mohd. Noor, Norzailawati; Zakariya, Khalilah; Ibrahim, Illyani; Nizarudin, Norhanis Diyana; N Murtaza, Fatin Farhana; Ab Rahman, Saifol Anwar (2021)
Website Application Survey Software of IIUM Land Use and Landscape Character Survey Tool (i-LULACAST) that are developed for the purpose of virtual survey for data collection Kajian Menigkatkan Imej Serta Identiti Bandar Diraja Pekan, Pahang. Also, this web app is developed in response to the constraint to conduct a face-to-face survey due to the current situation of the covid-19 pandemic